Genetic variants of PPAR-gamma coactivator 1B augment NLRP3-mediated inflammation in gouty arthritis. (25th October 2016) - Chang, Wan-Chun; Jan Wu, Yeong-Jian; Chung, Wen-Hung; Lee, Yun-Shien; Chin, See-Wen; Chen, Ting-Jui; Chang, Yu-Sun; Chen, Der-Yuan; Hung, Shuen-Iu
Abstract : Objective. Gout is characterized by recurrent attacks of arthritis with hyperuricaemia and urate crystal-induced inflammation. Although urate transporters are known as risk factors, the immunogenetics of gouty inflammation remains unclear. This study aimed to investigate the genetic association between immune/metabolism regulators and gout. Methods. We enrolled 448 gout patients and 943 population controls from Taiwan; all were Han Chinese. We screened association between gout and 22 variants of candidate genes, including NLRP3, caspase 1, peroxisome proliferator-activated receptor-γ, proliferator-activated receptor-γ coactivator 1α ( PPARGC1A ) and 1β ( PPARGC1B ). The association was validated by replication and combined-sample analyses. Functional assays were performed by quantitative PCR, ELISA, siRNA knockdown and transfection using THP-1 cells, peripheral blood mononuclear cells and synovial cells from patients. Results. Gouty arthritis exhibited significant association with variants of peroxisome PPARGC1B, which included a missense single nucleotide polymorphism, rs45520937 [P = 6.66 × 10 −9 ; odds ratio (95% CI): 1.85 (1.51, 2.28)]. Expression of PPARGC1B and NLRP3 was induced in urate crystal-activated THP-1, peripheral blood mononuclear cells and synovial cells from gout patients in acute stage. siRNA knockdown of PPARGC1B upregulated NLRP3 in urate crystal-activated macrophages. Compared with the wild-type carriers, patients with the risk A allele of rs45520937 showed statistically increased NLRP3 (P = 0.044) and plasma IL-1β (P = 0.006). Transfection of PPARGC1B cDNA with rs45520937 A allele to macrophages significantly augmented the expression of NLRP3 and IL-1β. Conclusion. Genetic variants of PPARGC1B are significantly associated with gout, and a missense single nucleotide polymorphism, rs45520937, augments NLRP3 and IL-1β expression. These data suggest that variants of PPARGC1B, a regulator of metabolism and inflammation, contribute to the pathogenesis of gouty arthritis.